From Information to Participation: Social Media Engagement Strategies in 2026 Portuguese Presidential Race - Duarte, A.; Oliveira, H.; Leandro, A. (Classical Legacy and Contemporary Challenges: A Multidisciplinary Approach to Education, Communication, and Law, 2026)
The growing centrality of social media platforms in modern daily life, extending to countless spheres of daily life and, consequently, also to political and party communication, has reshaped how candidates interact with citizens and how citizens experience political campaigns. Platforms like Instagram have become arenas where visibility, affect, and performance intersect with attention metrics, thus reconfiguring the logics of political communication. In presidential elections, given their one-person nature, candidates not only disseminate political messages but also compete for symbolic proximity, authenticity, and engagement, navigating algorithmic environments that privilege visual narrative and interaction cues. Based on the concept of Social Media Engagement Behavior (SMEB) proposed by Dolan and colleagues (2015; 2019), this study investigates how the five main candidates for the Presidency of the Portuguese Republic (according to all public surveys available to date) used Instagram during the pre-campaign and campaign period, from December 22, 2025, to January 16, 2026. This investigation, therefore, focuses on how the candidates employed informative, relational, and participatory strategies to promote engagement, examining both the characteristics of the content and the behavioral responses of users. The article adopts a mixed-method content analysis, integrating quantitative coding with qualitative interpretation. The objective is not simply to measure engagement, but to understand how it is strategically produced through content design and how the audience specifically responds to each post. To guide this investigation, the literature review addresses four interrelated domains: (1) Instagram as a socio-technical environment; (2) social networks and the dynamics of engagement; (3) engagement in digital political communication; and (4) content analysis as a methodological framework for social media research. Based on this, the study presents the following illustrative research questions and hypotheses: RQ1: How do presidential candidates use Instagram resources to construct informative, relational, and participatory messages? RQ2: How do different types of engagement-oriented content relate to variations in audience reactions (likes, comments, shares)? Furthermore, and resulting from the literature review conducted, 2 hypotheses were formulated, namely: H1: Posts that emphasize relational cues (authenticity, proximity, behind-the-scenes access) generate higher levels of affective engagement than strictly informative posts. H2: Participatory stimuli (calls to action, invitations to interaction) are associated with higher levels of interactive behaviors (comments and sharing). By systematically comparing communication styles and engagement outcomes, this study seeks to contribute to a deeper understanding of political communication practices in social media and their effectiveness in stimulating citizen engagement in contemporary electoral contexts, using the pre-campaign period for the presidential elections in Portugal as a basis for analysis.